Public Economy Analysis in Electricity-based Transportation in Jakarta: Dilemmas and Costs - Nur Hidayat, Achmad (KnE Social Sciences, 2024)
Transportation is of the major component when it comes to city’s economy. In Jakarta, the dense and fast-growing Indonesian capital, fossil-fuel-based motor vehicles account for most of the greenhouse gas emissions and air pollution. Therefore, implementing electricity-based transportation has become very relevant and important for Jakarta to create a more sustainable environment. The main objective of this research is to conduct a public economic analysis of the development and operation of electricity-based transport in Jakarta, focusing on the dilemmas and related costs. The research uses qualitative approaches, combining document analysis, interviews with related stakeholder documents, and economic models to calculate the related costs and benefits. The results show that despite the high initial costs associated with infrastructure and vehicle acquisition, electricity-based transport has the potential to generate significant long-term economic, environmental, and social benefits. The result can provide important insights for policymakers on the economic implications of the development of electricity-based transportation in Jakarta. To obtain such benefits, significant initial investments, strong policy support, and collaboration between the public and private sectors are needed. Keywords: public economy, context and electricity-based transportation, interests